Six amendments : how and why we should change the Constitution - Stevens, John Paul, 1920-2019- (Little, Brown and Company, 2014)
A retired Supreme Court Justice describes how the U.S. Constitution needs to be amended, detailing six specific changes that will protect democracy and ensure the safety and well-being of all American citizens.